A special flame-retardant B1-grade optical cable and a preparation method thereof
Patent Information
- Application Number
- CN202611499692.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
[0008]本发明在于提供一种阻燃B1级特种光缆及其制备方法,至少解决现有技术中存在的多层阻燃结构因热膨胀系数失配导致的界面脱粘与裂纹扩展、松套管加工性与阻燃性难以兼顾、阻燃协效剂阻燃效率与抑烟性能难以协调问题
1、本发明通过在铝塑复合带表面设置孔径为1~3μm的微孔结构,当火灾高温使陶瓷化硅橡胶层裂解转变为粘流态并发生体积膨胀时,该粘流体在径向膨胀压驱动下进入微孔,随后原位陶瓷化形成贯穿微孔且端部凸起的“铆钉状”永久性物理锚固结构,通过锚固头机械卡止与颈部摩擦锁止的协同作用将陶瓷化层与金属复合带锚固为一体;同时微孔群将连续界面分割为众多微小区段,使陶瓷层与金属层因热膨胀系数差异产生的热失配应力在每个锚固点附近得到局部释放,有效阻碍了界面裂纹的连续扩展;此外,互锁界面的曲折路径有效延长了烟气从外部向缆芯的扩散路径,降低烟气侵入风险,确保多层阻燃结构在火灾全过程中保持几何完整性。
Smart Images

Figure CN123010209A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of optical cable technology, specifically to a flame-retardant B1-grade special optical cable and its preparation method. Background Technology
[0002] With the continuous improvement of my country's building fire safety standards, GB 31247-2014 "Classification of Combustion Performance of Cables and Optical Fibers" has put forward multi-dimensional and stringent requirements for the combustion performance of optical fiber products. B1-level flame-retardant optical fiber cables must simultaneously meet the comprehensive assessment of multiple indicators, including flame spread height (≤2.5m), peak heat release rate (≤30kW / m²), total heat release (≤15MJ within 1200s), peak smoke production rate (≤0.25m² / s), total smoke production (≤50m² within 1200s), combustion drip level (d0 level), and smoke toxicity level (t0 level).
[0003] There are still many technical problems that need to be solved in the process of achieving the B1 flame retardant rating for existing flame-retardant optical cables.
[0004] One issue is the thermal-mechanical mismatch and interfacial debonding in multi-layer flame-retardant structures. Existing flame-retardant optical cables typically employ a composite structure of a ceramicized silicone rubber layer and a metal composite tape (such as an aluminum-plastic composite tape). However, the coefficient of linear expansion of the ceramicized layer is approximately 1.2 × 10⁻⁶. -4 At / ℃, the linear expansion coefficient of the metal composite strip is approximately 2.3×10. -5 Within a temperature rise range of 300-600℃, the interfacial thermal stress can reach 15-25 MPa, far exceeding the bending strength of the ceramicized layer, making interfacial cracking inevitable. Furthermore, traditional wrapping structures lose their binding force after the matrix resin melts at approximately 180-220℃, causing the expanded graphite layer to easily warp axially, forming channels for smoke gas flow. These core technical problems, such as interlayer delamination, high-temperature cracking, and the contradiction between flame retardancy and processing performance in loose tubes, severely restrict the reliability of B1-grade flame-retardant optical cables in fiber optic communication under fire conditions.
[0005] Secondly, it is difficult to simultaneously achieve both processability and flame retardancy in loose tubes. As a key component in optical cables that directly houses optical fibers, loose tubes present challenges. While ordinary PBT materials offer excellent processability and resistance to bending fatigue, they are flammable and easily melt and drip when exposed to fire, directly damaging the optical fiber. Although flame-retardant PC materials possess self-extinguishing properties, their narrow processing window and poor compatibility with optical fiber grease make it difficult to meet the comprehensive performance requirements of loose tubes on their own.
[0006] Thirdly, it is difficult to coordinate the flame-retardant efficiency and smoke-suppressing performance of flame-retardant synergists. To achieve flame-retardant effects, existing flame-retardant sheathing materials often add large amounts of inorganic flame retardants such as aluminum hydroxide and magnesium hydroxide, typically as high as 150-200 parts per part, leading to a significant decrease in the material's mechanical properties. Regarding the selection of flame-retardant synergists, current technologies mostly use antimony trioxide, which, while having a good flame-retardant synergistic effect, produces a large amount of smoke during combustion, making it difficult to meet the stringent requirements of B1 grade for smoke production rate and total smoke output.
[0007] Therefore, there is an urgent need for a new type of B1-grade flame-retardant optical cable and its preparation method that can simultaneously solve the problems of debonding at the interface of the multi-layer structure, the contradiction of loose tube performance, and the insufficient smoke suppression of flame retardant synergists. Summary of the Invention
[0008] The present invention provides a flame-retardant B1 grade special optical cable and its preparation method, which at least solves the problems existing in the prior art, such as interface debonding and crack propagation caused by the mismatch of thermal expansion coefficients in multi-layer flame-retardant structures, difficulty in balancing the processability and flame retardancy of loose tubes, and difficulty in coordinating the flame retardant efficiency and smoke suppression performance of flame retardant synergists.
[0009] According to one aspect of the present invention, a flame-retardant B1-grade special optical cable is provided, comprising: Cable core; The oxygen-barrier and flame-retardant composite layer is composed of an inner layer of ceramicized silicone rubber and an outer layer of intumescent graphite flame-retardant tape. The inner layer of ceramicized silicone rubber covers the surface of the cable core, and the outer layer of intumescent graphite flame-retardant tape wraps around the outside of the inner layer of ceramicized silicone rubber. A metal composite tape wrapping layer is wrapped around the outer surface of the oxygen-barrier and flame-retardant composite layer; the metal composite tape wrapping layer is made of aluminum-plastic composite tape with micropores on the surface, the pore size of the micropores is 1~3μm, and the longitudinal wrapping overlap rate is 28%~32%; under high temperature conditions, the ceramicized silicone rubber inner layer expands due to heat and embeds into the micropores to form a mechanical interlocking interface. A flame-retardant inner sheath covers the outer surface of the metal composite strip wrapping layer; An armor layer is applied to the outer surface of the flame-retardant inner sheath. A flame-retardant outer sheath covers the outer surface of the armor layer; Both the flame-retardant inner sheath and the flame-retardant outer sheath are made of ultraviolet-irradiated cross-linked low-smoke halogen-free flame-retardant polyolefin material. The ultraviolet-irradiated cross-linked low-smoke halogen-free flame-retardant polyolefin material comprises the following components in parts by weight: 40-50 parts of polyethylene-vinyl acetate resin, 18-22 parts of elastomer resin, 15-20 parts of compatibilizer resin, 8-12 parts of polyethylene resin, 2.5-3.5 parts of photoinitiator, 3.5-4.5 parts of cross-linking agent, 1-2 parts of antioxidant, 1-2 parts of lubricant, 160-190 parts of modified aluminum hydroxide flame retardant, and 30-40 parts of flame retardant synergist; the flame retardant synergist is diethylaluminum hypophosphite.
[0010] As an alternative, the cable core includes a central reinforcing member, multiple loose tubes twisted around the central reinforcing member, and a water-blocking material filling the gaps in the cable core; the loose tubes are a double-layer co-extruded composite structure, including an inner loose tube layer and an outer loose tube layer, wherein an optical fiber bundle is placed in the inner loose tube layer and filled with fiber grease.
[0011] As an alternative, the inner layer of the loose tube is made of PBT material, and the outer layer of the loose tube is made of flame-retardant modified PC material and doped with 6wt%~9wt% cage-like polysilsesquioxane.
[0012] As an optional solution, the outer layer thickness of the loose sleeve is 0.18~0.22mm, and the inner layer thickness of the loose sleeve is 0.28~0.32mm.
[0013] As an optional solution, the extrusion thickness of the ceramicized silicone rubber inner layer is 0.9~1.2mm.
[0014] As an alternative, the micropores are formed by laser drilling or chemical etching, and the pore density of the micropores is 2000~4000 pores / cm².
[0015] As an optional approach, the irradiated gel content of the ultraviolet-irradiated crosslinked low-smoke halogen-free flame-retardant polyolefin material is 65%~75%.
[0016] According to another aspect of the present invention, a method for preparing a flame-retardant B1-grade special optical cable is also provided, comprising: The inner and outer layers of the loose tube are extruded simultaneously and wrapped around the optical fiber bundle using a double-layer co-extrusion process to form a double-layer co-extruded loose tube. Multiple loose tubes are twisted together with the central reinforcing member in an SZ twisting manner to form the cable core, and water-blocking material is filled in the gaps between the cable cores. Ceramicized silicone rubber is extruded onto the surface of the cable core using an extrusion mold. After cooling, it forms an inner layer of ceramicized silicone rubber. An expanded graphite flame-retardant tape is then wrapped around the inner layer of ceramicized silicone rubber to form an oxygen-barrier flame-retardant composite layer. An aluminum-plastic composite tape with micropores on its surface is longitudinally wrapped around the outside of the oxygen-barrier and flame-retardant composite layer to form a metal composite tape wrapping layer. A flame-retardant inner sheath is formed by melt extruding a low-smoke, halogen-free flame-retardant polyolefin material containing a flame-retardant synergist and cross-linking it with ultraviolet light in an extruder. After extrusion and cross-linking with ultraviolet light, an armor layer is applied, and then a flame-retardant outer sheath is extruded and cross-linked with ultraviolet light to obtain a flame-retardant B1 grade special optical cable.
[0017] As an optional solution, the co-extrusion temperature of the double-layer co-extruded loose tube is 265~275℃, and the extrusion temperature of the ceramicized silicone rubber inner layer is 90~110℃. The irradiation dose of the ultraviolet crosslinking is 28~32kGy, the ultraviolet wavelength is 310~380nm, and the lamp power density is 70~90W / cm.
[0018] As an alternative, the twisting pitch of multiple loose tubes twisted with the central reinforcing member is 12 to 14 times the outer diameter of the twist.
[0019] The beneficial effects of this invention are as follows: 1. This invention creates a microporous structure with a pore size of 1-3 μm on the surface of the aluminum-plastic composite strip. When the high temperature of a fire causes the ceramicized silicone rubber layer to decompose and transform into a viscous flow state and undergo volume expansion, the viscous flow enters the micropores under the drive of radial expansion pressure. Subsequently, in-situ ceramicization forms a permanent physical anchoring structure with a "rivet-like" shape that penetrates the micropores and protrudes at the ends. The ceramicized layer and the metal composite strip are anchored together by the synergistic effect of the mechanical locking of the anchor head and the friction locking of the neck. At the same time, the micropore group divides the continuous interface into numerous small segments, allowing the thermal mismatch stress caused by the difference in thermal expansion coefficients between the ceramic layer and the metal layer to be locally released near each anchoring point, effectively hindering the continuous propagation of interface cracks. In addition, the tortuous path of the interlocking interface effectively extends the diffusion path of smoke from the outside to the cable core, reducing the risk of smoke intrusion and ensuring that the multi-layer flame-retardant structure maintains its geometric integrity throughout the fire process.
[0020] 2. This invention employs a PBT / flame-retardant modified PC double-layer co-extruded composite loose tube structure. The inner PBT layer ensures excellent processability and bending fatigue resistance, while the outer flame-retardant modified PC layer is doped with cage-like polysilsesquioxane (POSS). Utilizing the barrier effect of POS, which rapidly forms a nanoscale dense ceramic carbon layer on the material surface during combustion, the loose tube possesses intrinsic flame-retardant capability. Compared to ordinary flame-retardant PC loose tubes without POS, this invention's loose tube maintains excellent processability while effectively avoiding the risk of melting and dripping damage to the optical fiber upon contact with fire, overcoming the shortcomings of single-layer PBT (flammability) and single-layer PC (processing difficulties).
[0021] 3. This invention uses aluminum diethylphosphite as a flame retardant synergist, combined with modified aluminum hydroxide as the main flame retardant. Polyethylene-vinyl acetate resin, as the matrix resin, provides good flexibility and flame retardant containment capacity. The elastomer resin improves the material's impact resistance and elongation at break. The compatibilizer resin improves the interfacial compatibility between the polar flame retardant and the non-polar resin matrix. Modified aluminum hydroxide, as the main flame retardant, decomposes upon heating, releasing water of crystallization, absorbing a large amount of heat, and diluting combustible gases. It captures free radicals in the gas phase and promotes char formation in the condensed phase, producing a significant flame retardant synergistic effect. Simultaneously, its smoke production is significantly lower than that of traditional antimony trioxide. Compared to schemes using antimony trioxide as a flame retardant synergist, this invention maintains excellent flame retardant synergy while exhibiting significantly superior smoke suppression performance. Attached Figure Description
[0022] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention, and those skilled in the art can obtain other embodiments based on these drawings without creative effort.
[0023] Figure 1 This is a schematic cross-sectional view of the flame-retardant B1-grade special optical cable in an embodiment of the present invention.
[0024] Figure 2 This is a flowchart of the preparation method of flame-retardant B1-grade special optical cable in the embodiments of the present invention.
[0025] The labels in the above figures are as follows: 1. Central reinforcement; 2. Loose tube; 3. Optical fiber; 4. Water-blocking material; 5. Ceramicized silicone rubber inner layer; 6. Expandable graphite flame-retardant tape outer layer; 7. Metal composite tape wrapping layer; 8. Flame-retardant inner sheath; 9. Armor layer; 10. Flame-retardant outer sheath. Detailed Implementation
[0026] Embodiments of the present invention will now be described in more detail with reference to the accompanying drawings. While some embodiments of the present invention are shown in the drawings, it should be understood that the present invention can be implemented in various forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the present invention. It should be understood that the drawings and embodiments of the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention.
[0027] Example 1 Figure 1The image shows a flame-retardant B1 grade special optical cable, which, from the inside out, includes a cable core, an oxygen-barrier flame-retardant composite layer, a metal composite tape wrapping layer 7, a flame-retardant inner sheath 8, an armor layer 9, and a flame-retardant outer sheath 10.
[0028] Specifically, the cable core includes a central reinforcing member 1, multiple loose tubes 2 twisted around the central reinforcing member 1, and a water-blocking material 4 filling the gaps in the cable core; the loose tubes 2 are a double-layer co-extruded composite structure, including an inner loose tube layer and an outer loose tube layer, with an optical fiber bundle placed inside the inner loose tube layer and filled with fiber grease.
[0029] In this embodiment, the inner layer of the loose tube is made of PBT material, and the outer layer of the loose tube is made of flame-retardant modified PC material and doped with 6wt%~9wt% of cage-like polysilsesquioxane (POSS).
[0030] In this embodiment, the outer layer thickness of the loose sleeve is 0.18~0.22mm, and the inner layer thickness of the loose sleeve is 0.28~0.32mm.
[0031] In this embodiment, cage-shaped polysilsesquioxane (POSS) is a nanoscale cage-shaped organic-inorganic hybrid molecule with a cage-shaped core structure. During combustion, it can rapidly form a nanoscale dense ceramic carbon layer on the material surface, exerting a barrier effect of heat insulation and oxygen isolation.
[0032] Specifically, the oxygen-barrier flame-retardant composite layer is composed of a ceramicized silicone rubber inner layer 5 and an intumescent graphite flame-retardant outer layer 6. The ceramicized silicone rubber inner layer 5 covers the surface of the cable core, and the intumescent graphite flame-retardant outer layer 6 wraps around the outside of the ceramicized silicone rubber inner layer 5.
[0033] In this embodiment, the extrusion thickness of the ceramicized silicone rubber inner layer 5 is 0.9~1.2mm.
[0034] Specifically, the metal composite tape wrapping layer 7 is wrapped around the outer surface of the oxygen-barrier and flame-retardant composite layer; the metal composite tape wrapping layer 7 is made of aluminum-plastic composite tape with micropores on the surface, the pore size of the micropores is 1~3μm, and the longitudinal wrapping overlap rate is 28%~32%; under high temperature conditions, the ceramicized silicone rubber inner layer 5 expands due to heat and embeds into the micropores to form a mechanical interlocking interface.
[0035] In this embodiment, the micropores are formed by laser drilling or chemical etching, and the pore density of the micropores is 2000~4000 pores / cm².
[0036] It should be noted that the selection of the micropore size range is based on the following: When the pore size is less than 1 μm, the viscous precursor in the submicron channel suffers from a decrease in conformational entropy due to the confined space and difficulty in the rearrangement of the filler network, leading to an exponential increase in effective viscosity and loss of fluidity. The viscous fluid cannot effectively migrate into the pores to form a filling anchor. When the pore size is greater than 3 μm, the stress concentration factor at the pore edge increases nonlinearly with increasing pore size. This causes the stress concentration at the pore edge of the aluminum-plastic composite tape to exceed the material's high-temperature creep strength threshold during the high-temperature thermal shock stage, resulting in penetrating microcracks and deterioration of the oxygen barrier function. Here, "viscous flow state" refers to the flowable viscous system formed by mixing the oligomers produced by the high-temperature pyrolysis of the silicone rubber matrix with the ceramic filler.
[0037] Specifically, the flame-retardant inner sheath 8 is wrapped around the outer surface of the metal composite strip wrapping layer 7.
[0038] Specifically, the armor layer 9 covers the outer surface of the flame-retardant inner sheath 8.
[0039] Specifically, the flame-retardant outer sheath 10 covers the outer surface of the armor layer 9.
[0040] In this embodiment, both the flame-retardant inner sheath 8 and the flame-retardant outer sheath 10 are made of ultraviolet-irradiated cross-linked low-smoke halogen-free flame-retardant polyolefin material. The ultraviolet-irradiated cross-linked low-smoke halogen-free flame-retardant polyolefin material includes the following components in parts by weight: 40-50 parts of polyethylene-vinyl acetate resin, 18-22 parts of elastomer resin, 15-20 parts of compatibilizer resin, 8-12 parts of polyethylene resin, 2.5-3.5 parts of photoinitiator, 3.5-4.5 parts of cross-linking agent, 1-2 parts of antioxidant, 1-2 parts of lubricant, 160-190 parts of modified aluminum hydroxide flame retardant, and 30-40 parts of flame retardant synergist; the flame retardant synergist is diethylaluminum hypophosphite.
[0041] In this embodiment, the irradiation dose of the ultraviolet-irradiated crosslinked low-smoke halogen-free flame-retardant polyolefin material is 28~32kGy, and the gel content after irradiation is 65%~75%.
[0042] Example 2 Based on the same design concept, such as Figure 2 As shown, this embodiment also provides a method for preparing a flame-retardant B1-grade special optical cable, including: Step S21: Using a double-layer co-extrusion process, the inner layer and outer layer of the loose tube are simultaneously extruded and wrapped around the fiber bundle to form a double-layer co-extruded loose tube.
[0043] Step S22: Multiple loose tubes 2 and the central reinforcing member 1 are twisted together in an SZ twisting manner to form a cable core, and water-blocking material 4 is filled into the gaps between the cable cores.
[0044] Step S23: Ceramicized silicone rubber is extruded onto the surface of the cable core using an extrusion mold. After cooling, it forms an inner layer 5 of ceramicized silicone rubber. An expanded graphite flame-retardant tape is wrapped around the inner layer 5 of ceramicized silicone rubber in a wrapping manner to form an oxygen-barrier flame-retardant composite layer. Step S24: A metal composite wrapping layer 7 is formed by longitudinally wrapping an aluminum-plastic composite strip with micropores on its surface around the outside of the oxygen-barrier and flame-retardant composite layer.
[0045] Step S25: The ultraviolet-irradiated cross-linked low-smoke halogen-free flame-retardant polyolefin material containing flame retardant synergist is melt-extruded in an extruder and coated onto the outside of an aluminum-plastic composite tape with micropores to form a flame-retardant inner sheath 8. After extrusion and ultraviolet-irradiated cross-linking, an armor layer 9 is coated on it. Then, the flame-retardant outer sheath 10 is extruded and subjected to ultraviolet-irradiated cross-linking to obtain a flame-retardant B1 grade special optical cable.
[0046] In this embodiment, the co-extrusion temperature of the double-layer co-extruded loose tube is 265~275℃; the extrusion temperature of the ceramicized silicone rubber inner layer 5 is 90~110℃.
[0047] In this embodiment, the irradiation dose of the ultraviolet crosslinking is 28~32kGy, the ultraviolet wavelength is 310~380nm, and the lamp power density is 70~90W / cm.
[0048] In this embodiment, the twisting pitch of the multiple loose tubes 2 and the central reinforcing member 1 is 12 to 14 times the outer diameter of the twisting.
[0049] Example 3 This embodiment provides a flame-retardant B1-grade special optical cable and its preparation method.
[0050] Specifically, the preparation method of flame-retardant B1-grade special optical cable includes: Step S21: Using a double-layer co-extrusion process, the inner layer and outer layer of the loose tube are simultaneously extruded and wrapped around the optical fiber bundle at a co-extrusion temperature of 270℃ to form a double-layer co-extruded loose tube.
[0051] In this embodiment, the thickness of the PBT material used in the inner layer of the loose tube is 0.3 mm, falling within the range of 0.28~0.32 mm; the thickness of the flame-retardant modified PC material used in the outer layer of the loose tube is 0.2 mm, falling within the range of 0.18~0.22 mm, and the mass fraction of the doped cage-like polysilsesquioxane (POSS) is 8 wt%, falling within the range of 6 wt%~9 wt%.
[0052] In this embodiment, the fiber bundle includes 24 optical fibers 3, which are evenly distributed in 6 loose tubes 2.
[0053] Step S22: The six loose tubes 2 and the central reinforcing member 1 are twisted together in an SZ twisting manner to form a cable core, and water-blocking material 4 is filled into the gaps between the cable cores.
[0054] In this embodiment, the twisting pitch of the loose tube 2 and the center reinforcing member 1 when twisted in an SZ twisting manner is 80mm, which is about 13 times the outer diameter of the twisting; after twisting, the outer diameter of the cable core is 16mm.
[0055] Step S23: Using an extrusion mold, ceramicized silicone rubber is extruded onto the surface of the cable core at an extrusion temperature of 100°C. After cooling, an inner layer 5 of ceramicized silicone rubber is formed. Two layers of expanded graphite flame-retardant tape are then wrapped around the inner layer 5 of ceramicized silicone rubber to form an oxygen-barrier flame-retardant composite layer.
[0056] In this embodiment, the thickness of the ceramicized silicone rubber inner layer 5 is 1.0 mm.
[0057] In this embodiment, when the inner layer 5 of ceramicized silicone rubber is wrapped with two layers of expanded graphite flame-retardant tape, the overlap rate of each layer is 30%, which falls within the range of 28% to 32%.
[0058] Step S24: A metal composite wrapping layer 7 is formed by longitudinally wrapping an aluminum-plastic composite strip with micropores on its surface around the outside of the oxygen-barrier and flame-retardant composite layer.
[0059] In this embodiment, the micropore diameter is 2μm, falling within the range of 1~3μm, and the pore density is 3000 pores / cm², falling within the range of 2000~4000 pores / cm².
[0060] In this embodiment, the longitudinal overlap rate is 30%, and the overlap is fixed by hot melt adhesive.
[0061] Step S25: The low-smoke, halogen-free flame-retardant polyolefin material containing a flame retardant synergist is melt-extruded in an extruder and coated onto the outside of a microporous aluminum-plastic composite tape to form a flame-retardant inner sheath 8. After extrusion and ultraviolet irradiation crosslinking, an armor layer 9 is coated on it. Then, a flame-retardant outer sheath 10 is extruded and subjected to ultraviolet irradiation crosslinking to obtain a flame-retardant B1 grade special optical cable. The flame retardant synergist is diethyl aluminum hypophosphite.
[0062] In this embodiment, the ultraviolet-irradiated crosslinked low-smoke halogen-free flame-retardant polyolefin material includes: 45 parts of polyethylene-vinyl acetate resin, ranging from 40 to 50 parts; 20 parts of elastomer resin, ranging from 18 to 22 parts; 18 parts of compatibilizer resin, ranging from 15 to 20 parts; 10 parts of polyethylene resin, ranging from 8 to 12 parts; 3 parts of photoinitiator, ranging from 2.5 to 3.5 parts; 4 parts of crosslinking agent, ranging from 3.5 to 4.5 parts; 1.5 parts of antioxidant, ranging from 1 to 2 parts; 1.5 parts of lubricant, ranging from 1 to 2 parts; 180 parts of modified aluminum hydroxide flame retardant, ranging from 160 to 190 parts; and 35 parts of flame retardant synergist, ranging from 30 to 40 parts. The flame retardant synergist is diethylaluminum hypophosphite.
[0063] In this embodiment, the irradiation dose of the ultraviolet crosslinking is 30 kGy, falling within the range of 28~32 kGy; the ultraviolet wavelength is 365 nm, falling within the range of 310~380 nm; and the lamp power density is 80 W / cm, falling within the range of 70~90 W / cm.
[0064] In this embodiment, the flame-retardant inner sheath 8 has a thickness of 1.2 mm; the flame-retardant outer sheath 10 has a thickness of 1.5 mm.
[0065] In this embodiment, the armor layer 9 is a steel strip armor, which is wrapped with a double-layer gap, and each layer is 0.15mm thick.
[0066] After the above steps, a flame-retardant B1-grade special optical cable is obtained, with the cross-sectional structure as shown below. Figure 1 As shown.
[0067] To further verify the technical effect of the flame-retardant B1-grade special optical cable prepared in this embodiment, the combustion performance was tested in accordance with GB 31247-2014 "Classification of Combustion Performance of Cables and Optical Cables". The results of the combustion performance test are shown in Table 1.
[0068] Table 1 Combustion performance test results
[0069] As can be seen from the test results in Table 1, all the indicators of the prepared flame-retardant B1 grade special optical cable meet the flame-retardant requirements of GB31247-2014 B1 grade.
[0070] Meanwhile, the mechanical properties of the sheath of the prepared flame-retardant B1 grade special optical cable were tested in accordance with GB / T 2951.11-2008. The test results showed that the tensile strength and elongation at break of the UV-irradiated cross-linked sheath met the requirements of GB / T 2951.11-2008 standard and were significantly better than the uncross-linked comparative sample, indicating that UV irradiation cross-linking effectively improved the mechanical properties of the sheath.
[0071] To further verify the anchoring effect of the mechanical interlocking interface in this invention, a combustion test was conducted on the above-mentioned optical cable sample under standard fire source conditions specified in GB / T 31248-2014, with a flame temperature not lower than 750℃ and a continuous fire time of not less than 40 minutes. After the sample cooled naturally to room temperature, a universal testing machine was used to test the 180° peel strength between the metal composite tape wrapping layer 7 and the inner ceramicized silicone rubber layer at a peel speed of 50 mm / min, and the failure morphology of the peel interface was observed.
[0072] The sample using the microporous aluminum-plastic composite tape with a pore size of 1~3μm of the present invention can achieve a peel strength of 8~10N / cm. During the peeling process, the two cannot be completely separated. After forced peeling and damage, the ceramic layer exhibits a cohesive damage mode. A large amount of ceramic material remains in the form of "columnar broken nails" and is stuck inside the micropores. The diameter of the head of the remaining broken nails is significantly larger than the pore size, indicating that the damage occurs in the ceramic layer body rather than the interface.
[0073] As a control, the sample using ordinary aluminum-plastic composite tape without microporous treatment naturally delaminated the composite tape and ceramic layer under the same combustion conditions, with a peel strength of only 0.2 N / cm. The peel interface was smooth and flat, exhibiting typical brittle interface debonding failure. The control sample using microporous aluminum-plastic composite tape with a pore size of 0.5 μm had a peel strength of only 0.8 N / cm. There was no ceramic filler in the micropores, and only sporadic adhesion traces were present at the edge of the pore opening, failing to form geometric anchoring.
[0074] The above results show that the present invention achieves in-situ high-strength anchoring of the ceramicized silicone rubber inner layer 5 under high temperature in a fire through a 1~3μm microporous structure. The peel strength is increased from 0.2N / cm in the non-porous sample to 8~10N / cm, and the failure mode changes from interfacial debonding to cohesive failure of the ceramic layer.
[0075] Furthermore, the flame-retardant B1-grade special optical cable and its preparation method of this invention have widely available raw materials and mature, reliable processes, and can be industrially produced using existing optical cable production equipment, demonstrating good industrial applicability. This optical cable can be widely used in places with stringent fire safety requirements, such as rail transportation, high-rise buildings, data centers, petrochemical plants, and ships, and has broad market prospects.
[0076] Example 4 To verify the versatility of the technical solution of this invention under different process parameters and formulation conditions, the following test groups were set up based on Example 3 for verification. Parameters not listed in each test group are the same as in Example 3.
[0077] (1) Experimental group 1: The amount of flame retardant synergist added was 40 parts of aluminum diethylphosphite, and no other synergists were added; the irradiation dose of ultraviolet light crosslinking was 28 kGy, and the ultraviolet light wavelength was 315 nm.
[0078] (2) Experimental group 2: The amount of cage-shaped polysilsesquioxane (POSS) added was 6wt%; the extrusion thickness of the ceramicized silicone rubber inner layer 5 was 1.2mm; the overlap rate of the expanded graphite flame retardant tape was 35%; the micropore diameter was 3μm and the pore density was 2000 pores / cm²; the irradiation dose of the ultraviolet light crosslinking was 32kGy.
[0079] (3) Experimental group 3: The amount of cage-shaped polysilsesquioxane (POSS) added was 9wt%; the thickness of the PBT material used in the inner layer of the loose tube was 0.28mm, and the thickness of the flame-retardant modified PC material used in the outer layer of the loose tube was 0.22mm; the extrusion thickness of the ceramicized silicone rubber inner layer 5 was 0.9mm; the micropore diameter was 1μm, and the pore density was 4000 pores / cm²; the irradiation dose of the ultraviolet light crosslinking was 28kGy, and the ultraviolet light wavelength was 380nm; the lamp power density was 70W / cm.
[0080] (4) Experimental group 4: The amount of cage-shaped polysilsesquioxane (POSS) added was 7wt%; the thickness of the PBT material used in the inner layer of the loose tube was 0.32mm, and the thickness of the flame-retardant modified PC material used in the outer layer of the loose tube was 0.18mm; the extrusion thickness of the ceramicized silicone rubber inner layer 5 was 1.1mm; the micropore diameter was 1.5μm, and the pore density was 3500 pores / cm²; the irradiation dose of the ultraviolet crosslinking was 31kGy, and the ultraviolet wavelength was 340nm; the lamp power density was 85W / cm.
[0081] (5) Experimental group 5: The amount of the flame retardant synergist added was 30 parts of aluminum diethyl phosphite; the crosslinking agent was trimethylolpropane triacrylate (TMPTA); the photoinitiator was a benzophenone derivative (4-methylbenzophenone); the irradiation dose for crosslinking by ultraviolet light irradiation was 28 kGy.
[0082] Tests showed that all indicators of the flame-retardant B1-grade special optical cables prepared by the above-mentioned test institutes met the flame-retardant requirements of GB 31247-2014 B1 grade, with a combustion dripping level of d0 and a smoke toxicity level of t0.
[0083] Example 5 To verify the necessity and irreplaceability of the key technical features of this invention, eight comparative examples are set up in this embodiment for comparison with Example 3. Each comparative example is based on Example 3, changing only a single parameter while keeping all other conditions the same, as detailed below.
[0084] (1) Comparative Example 1: Verify the synergistic effect of the oxygen-barrier flame-retardant composite layer.
[0085] Comparison Object 1: The outer layer 6 of the intumescent graphite flame retardant tape is omitted, and only the inner layer of the ceramicized silicone rubber layer is retained.
[0086] Test results: The flame spread height, peak heat release rate, and peak smoke production rate exceeded the B1 level standard limits.
[0087] The test results show that the synergistic thermal insulation effect of the outer layer 6 of the intumescent graphite flame-retardant tape and the inner layer of the ceramicized silicone rubber layer makes an irreplaceable contribution to achieving the B1 grade standard. Although the inner layer of ceramicized silicone rubber alone can form a ceramic protective layer, its thermal insulation effect is insufficient, and heat can still be conducted to the cable core.
[0088] (2) Comparative Example 2: Verify the interface enhancement effect of microporous metal composite strip.
[0089] Comparison Object 2: Ordinary aluminum-plastic composite tape without microporous treatment is used to replace the surface microporous aluminum-plastic composite tape.
[0090] Test results: After the combustion test, obvious peeling and cracks appeared at the interface between the ceramicized silicone rubber layer and the metal composite strip. The smoke intrusion through the cracks caused the peak smoke production rate to exceed the B1 level standard limit.
[0091] The experimental results show that the mechanically interlocked interface formed by the microporous structure plays a key role in suppressing high-temperature interlayer delamination, and ordinary aluminum-plastic composite tapes without microporous treatment are difficult to maintain interface integrity under high-temperature fire conditions.
[0092] (3) Comparative Example 3: Verify the irreplaceability of POSS doping.
[0093] Comparison Object 3: The flame-retardant modified PC material used in the outer layer of the sleeve does not contain cage-like polysilsesquioxane (POSS), but only uses commercially available flame-retardant PC material containing phosphate ester flame retardants.
[0094] Test results: The peak heat release rate and peak smoke production rate exceeded the B1 level standard limit.
[0095] The experimental results show that the nanoceramization effect of cage-shaped polysilsesquioxane (POSS) has an irreplaceable contribution to the flame retardancy of loose sleeve tube 2, and ordinary flame retardant PC materials cannot achieve the same flame retardant effect with the same amount of addition.
[0096] (4) Comparative Example 4: Verify the superiority of ultraviolet light irradiation crosslinking over peroxide crosslinking.
[0097] Comparison Object 4: The flame-retardant inner sheath 8 and the flame-retardant outer sheath 10 are chemically cross-linked with peroxide, with 2 parts of DCP cross-linking agent added, a cross-linking temperature of 180℃, a cross-linking time of 15min, and the photoinitiator is removed from the sheath formulation.
[0098] Test results: The peak heat release rate slightly exceeded the B1 limit, and the residual crosslinking agent caused a significant decrease in the elongation at break after the sheath aged.
[0099] The test results show that peroxide chemical crosslinking requires high temperature conditions, which limits the speed of the production line. Furthermore, the residue of the crosslinking agent leads to insufficient long-term reliability, and its overall performance is inferior to that of ultraviolet irradiation crosslinking.
[0100] (5) Comparative Example 5: Verify the comprehensive advantages of ultraviolet light irradiation crosslinking compared with electron beam irradiation.
[0101] Comparison Object 5: The flame-retardant inner sheath 8 and the flame-retardant outer sheath 10 are cross-linked by electron accelerator irradiation with an irradiation dose of 30 kGy and an accelerator energy of 1.5 MeV.
[0102] Test results: The flame retardant indicators are comparable to those of Example 3, but the equipment investment cost is about 8 to 10 times that of the ultraviolet irradiation crosslinking equipment, the energy consumption is 3 to 5 times that of the ultraviolet irradiation crosslinking equipment, and the sheath turns yellow after irradiation, and the appearance does not meet the appearance requirements of communication optical cables.
[0103] The experimental results show that electron accelerator irradiation crosslinking equipment has high investment, high energy consumption, and poor appearance quality, and its overall advantages are not as good as ultraviolet irradiation crosslinking.
[0104] (6) Comparative Example 6: Verify the smoke suppression advantage of aluminum diethylphosphite compared with antimony trioxide.
[0105] Comparison Object 6: The flame retardant synergist used was antimony trioxide, with an addition amount of 35 parts.
[0106] Test results: The peak flame spread height and heat release rate were comparable to those of Example 3, but the peak smoke production rate and total smoke production exceeded the B1 level standard limit.
[0107] The test results show that aluminum diethylphosphite, while maintaining excellent flame retardant synergy, has significantly better smoke suppression performance than antimony trioxide, playing a key role in meeting the B1 low smoke requirements.
[0108] (7) Comparative Example 7: Verify the critical effect of ultraviolet irradiation dose.
[0109] Comparative object 7: The ultraviolet irradiation dose is 15 kGy, which is lower than the lower limit of the scope defined in this invention.
[0110] Test results: The cross-linking degree of the flame-retardant inner sheath 8 and the flame-retardant outer sheath 10 is significantly lower than that of the present invention. At high temperature, the flame-retardant inner sheath 8 and the flame-retardant outer sheath 10 melt and drip, the flame-retardant barrier fails, and the peak heat release rate exceeds the B1 level limit.
[0111] The test results show that when the ultraviolet irradiation dose is less than 28 kGy, the degree of crosslinking is insufficient, making it difficult to guarantee the B1 grade flame retardant performance.
[0112] (8) Comparative Example 8: Verify the critical effect of the lower limit of aperture.
[0113] Comparison Object 8: Microporous aluminum-plastic composite tape with a pore size of 0.5μm.
[0114] Test results: The peel strength was only 0.8 N / cm, the peel interface was macroscopically smooth, the micropores were empty and unfilled, and only a few traces of adhesion were found at the edge of the pore opening.
[0115] Experimental results show that when the pore size is less than 1 μm, the effective viscosity of the viscous precursor in the submicron channel increases exponentially due to the decrease in conformational entropy under confined space and the difficulty of packing network rearrangement. The viscous fluid cannot effectively migrate into the pore to form geometric anchorage, and only the rough pore wall provides a limited increase in frictional resistance, thus failing to achieve the mechanical interlocking effect described in this application.
[0116] It should be noted that the term "comprising" and its variations used in the embodiments of this invention are open-ended, meaning "including but not limited to". The term "based on" means "at least partially based on". The term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one additional embodiment"; the term "some embodiments" means "at least some embodiments". The modifications of "one" and "a plurality" mentioned in the embodiments of this invention are illustrative and not restrictive, and those skilled in the art should understand that unless explicitly indicated otherwise in the context, they should be understood as "one or more".
[0117] The term "embodiment" in this specification refers to a specific feature, structure, or characteristic described in connection with an embodiment that may be included in at least one embodiment of the invention. The appearance of this phrase in various places throughout the specification does not necessarily imply the same embodiment, nor does it imply independence or alternativeity from other embodiments. The various embodiments in this specification are described in a related manner, with reference to each other for similar or identical parts. In particular, for apparatus, device, and system embodiments, since they are substantially similar to method embodiments, the description is relatively simple, and relevant details are referred to in the description of the method embodiments.
[0118] The above embodiments merely illustrate several implementation methods of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of protection. It should be noted that those skilled in the art can make various modifications and improvements without departing from the inventive concept of the present invention, and these all fall within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the appended claims.
Claims
1. A flame-retardant B1-grade special optical cable, characterized in that, include: Cable core; The oxygen-barrier flame-retardant composite layer is composed of a ceramicized silicone rubber inner layer (5) and an intumescent graphite flame-retardant outer layer (6). The ceramicized silicone rubber inner layer (5) covers the surface of the cable core, and the intumescent graphite flame-retardant outer layer (6) wraps around the outside of the ceramicized silicone rubber inner layer (5). A metal composite tape wrapping layer (7) is wrapped around the outer surface of the oxygen-barrier flame-retardant composite layer; the metal composite tape wrapping layer (7) is made of aluminum-plastic composite tape with micropores on the surface, the pore size of the micropores is 1~3μm, and the longitudinal wrapping overlap rate is 28%~32%; under high temperature conditions, the ceramicized silicone rubber inner layer (5) expands due to heat and embeds into the micropores to form a mechanical interlocking interface; A flame-retardant inner sheath (8) covers the outer surface of the metal composite strip wrapping layer (7); An armor layer (9) covers the outer surface of the flame-retardant inner sheath (8); A flame-retardant outer sheath (10) covers the outer surface of the armor layer (9); Both the flame-retardant inner sheath (8) and the flame-retardant outer sheath (10) are made of ultraviolet-irradiated cross-linked low-smoke halogen-free flame-retardant polyolefin material. The ultraviolet-irradiated cross-linked low-smoke halogen-free flame-retardant polyolefin material includes the following components in parts by weight: 40-50 parts of polyethylene-vinyl acetate resin, 18-22 parts of elastomer resin, 15-20 parts of compatibilizer resin, 8-12 parts of polyethylene resin, 2.5-3.5 parts of photoinitiator, 3.5-4.5 parts of cross-linking agent, 1-2 parts of antioxidant, 1-2 parts of lubricant, 160-190 parts of modified aluminum hydroxide flame retardant, and 30-40 parts of flame retardant synergist. The flame retardant synergist is diethylaluminum hypophosphite.
2. The flame-retardant B1-grade special optical cable according to claim 1, characterized in that, The cable core includes a central reinforcing member (1), multiple loose tubes (2) twisted around the central reinforcing member (1), and a water-blocking material (4) filling the gaps in the cable core; the loose tube (2) is a double-layer co-extruded composite structure, including an inner loose tube layer and an outer loose tube layer, wherein an optical fiber bundle is placed in the inner loose tube layer and filled with fiber grease.
3. The flame-retardant B1-grade special optical cable according to claim 2, characterized in that, The inner layer of the loose tube is made of PBT material, and the outer layer of the loose tube is made of flame-retardant modified PC material and doped with 6wt%~9wt% cage-like polysilsesquioxane.
4. The flame-retardant B1-grade special optical cable according to claim 2, characterized in that, The outer layer thickness of the loose sleeve is 0.18~0.22mm, and the inner layer thickness of the loose sleeve is 0.28~0.32mm.
5. The flame-retardant B1-grade special optical cable according to claim 1, characterized in that, The extrusion thickness of the ceramicized silicone rubber inner layer (5) is 0.9~1.2mm.
6. The flame-retardant B1-grade special optical cable according to claim 1, characterized in that, The micropores are formed by laser drilling or chemical etching, and the pore density of the micropores is 2000~4000 pores / cm².
7. The flame-retardant B1-grade special optical cable according to claim 1, characterized in that, The irradiated gel content of the ultraviolet-irradiated crosslinked low-smoke halogen-free flame-retardant polyolefin material is 65%~75%.
8. A method for preparing a flame-retardant B1-grade special optical cable, characterized in that, include: The inner and outer layers of the loose tube are extruded simultaneously and wrapped around the optical fiber bundle using a double-layer co-extrusion process to form a double-layer co-extruded loose tube. Multiple loose tubes (2) are twisted together with the central reinforcing member (1) in an SZ twisting manner to form a cable core, and water-blocking material (4) is filled in the gap between the cable cores. Ceramicized silicone rubber is extruded onto the surface of the cable core using an extrusion mold. After cooling, it forms an inner layer of ceramicized silicone rubber (5). An expanded graphite flame-retardant tape is wrapped around the inner layer of ceramicized silicone rubber (5) to form an oxygen-barrier flame-retardant composite layer. An aluminum-plastic composite tape with micropores on its surface is longitudinally wrapped around the outside of the oxygen-barrier and flame-retardant composite layer to form a metal composite tape wrapping layer (7). The flame-retardant polyolefin material containing flame retardant synergist is melt-extruded in an extruder and coated onto the outside of an aluminum-plastic composite tape with micropores to form a flame-retardant inner sheath (8). After extrusion and cross-linking by ultraviolet irradiation, an armor layer (9) is coated on it. Then, the flame-retardant outer sheath (10) is extruded and cross-linked by ultraviolet irradiation to obtain a flame-retardant B1 grade special optical cable.
9. The method for preparing the flame-retardant B1-grade special optical cable according to claim 8, characterized in that, The co-extrusion temperature of the double-layer co-extruded loose tube is 265~275℃, and the extrusion temperature of the ceramicized silicone rubber inner layer (5) is 90~110℃. The irradiation dose of the ultraviolet crosslinking is 28~32kGy, the ultraviolet wavelength is 310~380nm, and the lamp power density is 70~90W / cm.
10. The method for preparing the flame-retardant B1-grade special optical cable according to claim 8, characterized in that, The twisting pitch of the multiple loose tubes (2) and the central reinforcing member (1) is 12 to 14 times the outer diameter of the twisting.
